PENILAIAN KENYAMANAN TERMAL RUANGAN MENGGUNAKAN PMV (STUDI KASUS PERPUSTAKAAN SDN 27 PONTIANAK UTARA) - Candra Monica; Yudi Purnomo; Zairin Zain (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Pontianak city has tropical climate and crossed by the equator. This phenomenon has an impact on the level of thermal comfort in a room, especially in North Pontianak District which is close to 0˚ latitude. library of the Public Elementary School (SDN) 27 North Pontianak is one of the examples. This library is located on the equator with coordinates 0˚00˚07N 109˚20'02E which has high temperature and high humidity levels. This condition impact on bad thermal comfort. bad thermal comfort can affect the health of indoor activities. Therefore, the thermal comfort level needs to be research and provide a room's solution to achieve a neutral thermal comfort condition. This research measures the thermal comfort's variables on PMV (Predicted Mean Vote). The variables measured were air temperature, radiation temperature, humidity and wind speed, the observed variables were metabolic values and clothing insulation. The thermal comfort level will be calculated using the Center of Building Environment (CBE) Thermal Comfort Tool. The results of this research indicate that the level of thermal comfort in the library which is calculated using the CBE Thermal Comfort Tool have PMV value ranging 0,07 to 2,96. The value of thermal sensation in library is neutral to hot. thermal comfort conditions can be achieved by the application of cross ventilation.